Analisis Cyberbullying Dalam Undang-Undang Informasi Dan Tranksaksi Elektronik - Hijrah Eritama Saputra; Muhammad Rassya Abraridhandra; Muhammad Zahri Hermawan; Asep Suherman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Cyberbullying is a form of digital bullying that is increasingly prevalent in the information technology era, involving actions such as insults, threats, and defamation through electronic media. A legal analysis of this phenomenon in the Electronic Information and Transactions Law (ITE Law) Number 19 of 2016 in conjunction with Law Number 1 of 2024 shows the main provisions in Article 27 paragraph (3), Article 45 paragraphs (3) and (4), and Article 45B which criminalizes the electronic distribution of content containing insults, threats, or persecution. Perpetrators can be subject to imprisonment of up to 6 years and/or a fine of IDR 1 billion, with a normative legal approach that integrates the Criminal Code as a complement. However, implementation challenges include the weakness of digital evidence, freedom of expression, and the need for restorative justice for child victims. This study recommends a revision of the ITE Law to clarify the definition of cyberbullying and victim protection mechanisms, for the sake of effective law enforcement in Indonesia.